Pengaruh Penambahan Jalur Terhadap Operasi Kereta Api Jarak Jauh (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2022)
Line 5 of the Bekasi Station Emplacement is a new line from the addition of a Double Double Track at the Bekasi Station Emplacement which will later be used as a direct train line with a maximum speed of 100 km/hour. The existence of 10 fixed curves and 2 temporary arches on line 5 needs to be evaluated for feasibility so that it can be crossed by trains at high speed. The evaluation is carried out in the form of an evaluation of the horizontal curve geometry which includes the evaluation of the minimum radius, rail elevation, the value of the bow arrow, and the allowable operating speed of the train. In addition, periodic maintenance plans can also be determined based on the analysis carried out on the horizontal bending radius. This evaluation is based on the Minister of Transportation Regulation No. 60 of 2012. From the evaluation for curves crossed by a train with a speed of 100 km/hour, all curves still meet the minimum radius requirements. While the 2 temporary arches are used to limit the speed of the train during the construction of the line, which will later be dismantled. In the evaluation of rail elevation all arches are eligible for outer rail elevation. Furthermore, an analysis of the actual value of bow arrows is also carried out in the field. From the analysis carried out, the arc needs to be adjusted to the specified arrow value.